2019
DOI: 10.1002/jgc4.1078
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in knowledge and attitudes about genetic testing in the US: Systematic review

Abstract: Precision medicine has grown over the past 20 years with the availability of genetic tests and has changed the one‐size‐fits‐all paradigm in medicine. Precision medicine innovations, such as newly available genetic tests, could potentially widen racial and ethnic disparities if access to them is unequal and if interest to use them differs across groups. The objective of this systematic review was to synthesize existing evidence on racial and ethnic differences in knowledge of and attitudes toward genetic testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 61 publications
5
72
0
Order By: Relevance
“…Research in other healthcare contexts shows racial/ethnic minorities have more concerns about genetic testing and precision medicine than Whites, believing genetic testing or precision medicine may be misused, lead to racial discrimination, or do more harm than good (21,22). However, preliminary findings support the acceptability of precision approaches for smoking among minorities.…”
Section: Introductionmentioning
confidence: 89%
“…Research in other healthcare contexts shows racial/ethnic minorities have more concerns about genetic testing and precision medicine than Whites, believing genetic testing or precision medicine may be misused, lead to racial discrimination, or do more harm than good (21,22). However, preliminary findings support the acceptability of precision approaches for smoking among minorities.…”
Section: Introductionmentioning
confidence: 89%
“…When evaluating comprehension by language in which the education was conducted, Spanish‐speaking participants scored significantly lower at pre‐test than did English speakers. Recent large national studies assessing knowledge surrounding genetic testing found that compared to Whites, minorities are less knowledgeable of genetic testing (Canedo et al, 2019; Haga, O'Daniel, Tindall, Lipkus & Agans, 2012; Singer, Couper, Raghunathan, Van Hoewyk & Antonucci, 2008). A retrospective evaluation of the General Social Survey at three time points (1990, 1996, and 2004) showed that while the proportion of respondents claiming to know ‘a great deal’ about genetic testing has increased (from 12.8% in 1990 to 18.1% in 2004), 67.4% of respondents know ‘not very much’ and 14.1% know ‘nothing at all’.…”
Section: Discussionmentioning
confidence: 99%
“…How low educational attainment, poor English proficiency, and limited health literacy and numeracy (Giuse et al, 2016) affect the understanding of complex genetic information and, thus, the uptake of these new treatments is of great concern. Accumulating evidence demonstrates that culturally diverse populations have limited understanding of genetics and genetic testing and are concerned about the purpose of genetic testing and the information this testing provides (Canedo, Miller, Myers & Sanderson, 2019). Minorities fear genetic discrimination and worry how this information may be used/misused (Catz et al, 2005; Hamilton et al, 2016), which impacts genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the term "precision medicine" among adults in the US is low, estimated at less than 25% in a recent study [9], even though approximately 80% of adults in the U.S. report that they have heard of genetic tests, which are a key component of PM [10]. A recent systematic review of studies published through 2017 [11] identified no studies that compared racial/ethnic differences in awareness of PM, though one study found no difference between Blacks and Whites in awareness of the related term "personalized medicine" [12]. This review also found Blacks and Hispanics/Latinos had lower factual knowledge about PM and more concerns about genetic testing compared to Whites.…”
Section: Introductionmentioning
confidence: 99%